Integration of spatial and temporal information during floral induction in arabidopsis - Wigge, Philip A.; Lohmann, Jan U. (Science, 2005)
Flowering of Arabidopsis is regulated by several environmental and endogenous signals. An important integrator of these inputs is the FLOWERING LOCUS T (FT) gene, which encodes a small, possibly mobile protein. A primary response to floral induction is the activation of FT RNA expression in leaves. Because flowers form at a distant site, the shoot apex, these data suggest that FT primarily controls the timing of flowering. Integration of temporal and spatial information is mediated in part by the bZIP transcription factor FD, which is already expressed at the shoot apex before floral induction. A complex of FT and FD proteins in turn can activate floral identity genes such as APETALA1 (AP1).